(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Recently, concerns have been raised regarding antimicrobial activity of the nanoparticle against the plant pathogenic fungi and increases in seed germination indices. The biosynthesis of silver nanoparticle from Trichoderma viride was very rapid and took 12 h at 30 0 c when cell free extract of the Trichoderma viride was used. The bio molecule secreted by Trichoderma viride was capable to synthesis and stabilize the particles. UV-Spectroscopy showed maximum surface Plasmon resonance at 444 nm. SEM showed polydisperse polyhedral and tetrahedral shape of nanoparticles (5-10μm). XRD pattern showed strong peak in entire spectrum at 1344. The biosynthesized silver nanoparticle proved efficient antifungal activity against plant pathogenic fungi Fusarium oxysporum which inhibit the 80-90% growth of fungal pathogen which causes Fusarium wilt in tomato. Biosynthesized silver nanoparticle proved significant impact on germination of Fenugreek seeds. The true benefit of the silver nanoparticle application it enhance the seed germination indices and resistance to plant pathogenic fungi.